(untitled) (Journal of Asian Development Studies, 2025)
The tension between state sovereignty and international human rights obligations has increasingly defined border governance in the 21st century. This study examined how restrictive security measures, intended to regulate migration and protect national borders, frequently conflicted with the protection of asylum seekers’ rights and the dignity of migrants. The research aimed to investigate the extent to which border security could be reconciled with human rights protections and to identify pathways for more balanced governance. A qualitative methodology was employed, relying on thematic analysis of policy documents, NGO reports, and migrant narratives. This design enabled a deeper understanding of the discourses and practices surrounding border securitization and asylum systems across multiple contexts. The results revealed three dominant themes: (1) the securitization of borders through militarization, surveillance, and externalization; (2) the gaps between international human rights frameworks and domestic implementation; and (3) the lived consequences of restrictive practices on migrants and asylum seekers. Evidence also suggested the possibility of reconciliation through humanitarian corridors, sponsorship programs, and the ethical regulation of technologies. The study concluded that human rights and sovereignty are not inherently contradictory; instead, they require deliberate efforts to balance security with protection. Future directions included cross-regional comparisons, greater integration of migrant voices, and an investigation into how climate change and digital technologies would impact the reshaping of border governance and human rights.